Requiem for a Dream: Academic Freedom under Threat in Democracies - Craciun, Daniela; Mihut, Georgiana (International Higher Education, 2017)
Academic freedom is both a core value and a governing principle of higher education institutions. However, more recently, governments in places generally deemed democratic have labeled universities as threats. The recent legislative change in Hungary represents a particularly worrying example.